Public acceptance of microbiome management strategy in dairy calves: a European survey on colostrum, probiotic provision and prolonged cow-calf contact - A. Ait Sidhoum; A. Stygar; F. Bedoin; J.K. Niemi (Animal)
The microbiome plays a crucial role in the calves’ early stages of life. Several management practices can be considered to enhance the development and composition of the microbiome in calves. However, their social acceptance is largely unknown. The aim of this study was to investigate the public acceptance of innovative microbiome management practices aimed at improving the health and welfare of calves and to assess the factors influencing these levels of acceptance. Data used in the analysis were obtained from an online survey conducted in July 2023. The final sample consists of 3 220 citizens from four EU countries (Finland = 813, France = 803, Ireland = 801 and Poland = 803). Participants were asked to assess four management practices designed to improve calves’ health and welfare: (1) using colostrum, (2) providing mix probiotics powder, (3) providing probiotics as yogurt or kefir and (4) prolonged cow-calf contact. Participants were provided with different levels of information: one group received only a short description of the intervention, while the other group received both the intervention description and information on aspects such as potential costs and environmental impact of the intervention. Participants were asked to rate the acceptance on a standardised scale ranging from 1 to 5, with 1 indicating “strongly agree” and 5 indicating “strongly disagree”. Additionally, the participants were questioned about their socio-demographic background (e.g. age, education). They were also asked to provide their perspectives on various dimensions concerning familiarity with farming and microbiome, food safety, environmental awareness, cost consideration, and cultural perspective of consuming dairy products. Obtained data were analysed using the ordinary least squares regression model. The findings reveal that prolonged cow-calf contact was the most acceptable measure among tested interventions in all countries (79% of responders agreed or strongly agreed). Attitudinal and socio-economic variables were found to have a differential effect across the studied management strategies. For instance, individuals with greater familiarity with farming systems and microbiomes were more inclined to accept all four interventions, while women, compared to men, showed higher acceptance of prolonged cow-calf contact. Results also indicate that the provision of additional information to the participants was associated with a decrease in the acceptance of the measures. In conclusion, the public’s perceptions regarding microbiome management strategies in dairy calves are shaped by complex factors. Also, our discussion emphasises the importance of clarity and transparency of messages, ethical dissemination of scientific knowledge, and the necessity for balanced and coherent communication.